2010
DOI: 10.4161/cib.3.6.13137
|View full text |Cite
|
Sign up to set email alerts
|

The “acrosomal synapse”

Abstract: Mammalian spermatozoa are highly polarized cells composed of two morphological and functional units, each optimized for a special task. Although the apparent division into head and tail may as such represent the anatomical basis to avoid random diffusion of their special sets of signaling proteins and lipids, recent findings demonstrate the presence of lipid raft-derived membrane platforms and specific scaffolding proteins, thus indicating that smaller sub-domains exist in the two functional units of male germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…Moreover, colocalization of IP 3 -R and TPC1 in detergent-resistant lipid raft platforms (Supplemental Figure S6) was observed. These lipid rafts embody a membrane-organizing principle of spatial sequestration, which leads to a subcellular concentration of components of the secretory machinery at the “acrosomal synapse” ( Zitranski et al. , 2010 ), the posterior region of the sperm head ( Gadella et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, colocalization of IP 3 -R and TPC1 in detergent-resistant lipid raft platforms (Supplemental Figure S6) was observed. These lipid rafts embody a membrane-organizing principle of spatial sequestration, which leads to a subcellular concentration of components of the secretory machinery at the “acrosomal synapse” ( Zitranski et al. , 2010 ), the posterior region of the sperm head ( Gadella et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2010 ), the posterior region of the sperm head ( Gadella et al. , 2008 ; Nixon and Aitken, 2009 ; Zitranski et al. , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors [33] demonstrated a presence of N-methyl-D-aspartate (NMDA) glutamate receptor NR2B and sodium-dependent glutamate transporter GLT1 in mouse and human sperm and showed that mouse sperm possessed the glutamate uptake property in similar way as brain did. Due to the fact that the acrosome vesicle exocytosis displays similar physiology with the active zone of the presynaptic terminal in neurons where neurotransmitter vesicle fusion occurs, and thus may be termed "acrosomal synapse" [34], the research from the field of neuroscience is relevant to sperm reproductive physiology.…”
Section: Sperm Chemotactic Responsiveness To L-glutamatementioning
confidence: 99%
“…Both the DRM of sperm as well as this apical sperm head surface are rafts that aggregate and are extremely highly enriched in zona pellucida and/or cumulus binding protein complexes (van Gestel et al 2005a ; 2007 ; Nixon and Aitken 2009 ; Nixon et al 2009 ; 2011 ; Reid et al 2011 ; Bromfield and Nixon 2013 a, 2013b ; Caballero et al 2012 ; Jones et al 2010 ; Tanphaichitr et al 2007 ). The same surface area contains SNARE proteins (Tsai et al 2007 ), which are involved in the docking of the acrosome during sperm capacitation (Ackermann et al 2008 ; Tsai et al 2010 , 2012 ; Zitranski et al 2010 ). Interestingly, the association of CDC42 and the oligomerization of caveolin-1 have been described (Baltiérrez-Hoyos et al 2012 ) and also, the involvement of CDC42 in lipid raft-mediated synaptic delivery has recently been reported (Brachet et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%